Evaluation of Toxoplasma gondii IgM and IgG Seropositivities in Serum Samples Sent from Pediatric and Adult Hematology/Oncology Outpatient Clinics - Ayfer Bakır; Mustafa Guney (Medical Laboratory Technology Journal, 2020)
Toxoplasmosis, despite its mild course in immunocompetent individuals, it may have a more severe course in immunosuppressed patients such as hematology and oncology patients. This study aimed to contribute to the importance of that issue by evaluating the seropositivity rates of Toxoplasma gondii (T. gondii) in Hematology and Oncology patients and sharing the data obtained. Serum samples sent from pediatric and adult Hematology/Oncology outpatient clinic to the Microbiology Laboratory between January 2017 and August 2019 were analysed using Architect Toxo IgG and IgM Reagent Kit with chemiluminescent microparticular enzyme immunoassay method on Architect system. A total of 673 patient samples belonging to 131 pediatric patients and 542 adult patients were analysed in the study. Median age of the study group was 29 (range: 0 - 83) and 53.5% of them were male. While T. gondii IgM positivity was 8% IgG positivity was 28.7%. T. gondii IgG seropositivities in male and female patients were 27.2% and 30.4% respectively (p = 0.44). T. gondii IgM seropositivities in pediatric and adult patients were 6.9% and 8.3% respectively and IgG seropositivities were 24.4% and 29.7% (p = 0.78 and p = 0.46 respectively). T. gondii IgM positivity was found as 8% and IgG positivity as 28.7% in the study group. In conclusion, data obtained from the study were in compliance with both domestic and foreign data and the highest rate of IgM and IgG seropositivity was found in patients with lymphoma.